Integration of Linear Constraints with a Temporal Logic Programming Language - Qian Ma; Zhenhua Duan; Mengfei Yang (2013 International Symposium on Theoretical Aspects of Software Engineering, 2013)
This paper investigates the integration of linear constraints with MSVL. To this end, we first define linear constraint statements and discuss related issues of the incorporation. Further, for calling SMT solvers to solve the newly introduced constraints, we give a translation algorithm from state programs in MSVL with linear constraints to SMT-LIB2.0 script language and then supply a solving procedure.